2013
DOI: 10.1245/s10434-013-3069-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Genetic Polymorphisms of Epidermal Growth Factor Receptor (EGFR) and Survival of Colorectal Cancer (CRC) Patients Treated with 5-Fluorouracil-Based Chemotherapy

Abstract: EGFR polymorphisms can serve as prognostic predictors for CRC patients receiving 5-FU-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…In contrast, another study reported that the wildtype GG genotype of rs2227983 is associated with CRC risk (31). Moreover, patients carrying wild-type genotype have been reported to have a poorer prognosis than those carrying the variant genotype (18,32). The rs2227983 polymorphism, an arginine-to-lysine amino acid substitution at codon 521 of the EGFR, has been shown to decrease ligand binding affinity, thus attenuating growth stimulation, tyrosine kinase activation and the induction of proto-oncogenes (33).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, another study reported that the wildtype GG genotype of rs2227983 is associated with CRC risk (31). Moreover, patients carrying wild-type genotype have been reported to have a poorer prognosis than those carrying the variant genotype (18,32). The rs2227983 polymorphism, an arginine-to-lysine amino acid substitution at codon 521 of the EGFR, has been shown to decrease ligand binding affinity, thus attenuating growth stimulation, tyrosine kinase activation and the induction of proto-oncogenes (33).…”
Section: Discussionmentioning
confidence: 96%
“…Disruption of TGFB signaling pathways by SMAD7 leads to various forms of tumorigenesis (34), thus increasing cancer risk. Moreover, other polymorphisms of the EGFR, including rs712829 and rs712830, have also been reported to be associated with CRC susceptibility (32).…”
Section: Discussionmentioning
confidence: 99%